THE INFLUENCE OF LIFESTYLE AND BRAND ON THE PURCHASE DECISION OF THRIFT CLOTHING PRODUCTS AMONG UIN MATARAM STUDENTS - Rabbaniyah, Fatimah; Nur’aeda, Nur’aeda (Laboratorium Riset Ekonomi, 2025)
This study aims to analyze the influence of lifestyle and brand on the purchase decisions of thrift clothing among students at UIN Mataram. A quantitative approach with an associative method was employed, involving 100 student respondents selected through purposive sampling. Data were collected via questionnaires and analyzed using SPSS version 26 software. The results indicate that lifestyle significantly affects purchase decisions (t-value 6.105 > t-table 1.984, sig. 0.000 < 0.05), as does brand (t-value 9.160 > t-table 1.984, sig. 0.000 < 0.05). Simultaneously, lifestyle and brand also have a significant impact on purchase decisions (f-value 42.075 > f-table 3.09, sig. 0.000 < 0.05). The coefficient of determination (Adjusted R²) of 0.453 shows that 45.3% of purchase decisions are influenced by lifestyle and brand, while 54.7% are influenced by other factors outside this study.